Fatigue in the Aged - Nelson, T. M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Levels of fatigue and mood dimensions were measured pre and post retirement. On the basis of a conflict analysis of fatigue originating from the conceptual framework established by Bartley and Chute (1969), it was hypothesized that fatigue levels would behigher pre than post retirement. The nature of the conflict involves negative attributions to retirement itself and to retirement as the advent of old age. Numerous studies support the widespread prevalence of such perceptions. Moreover, these perceptions seem to rest upon deeply rooted cultural definitions of old age and retirement practices operating in cultures based on Northern European models. The hypothesis was confirmed with a small sample of workers studied during a one-year period divided by point of retirement. More specifically, it was found that the two months prior to retirement were periods when fatigue levels were significantly higher in the early evening as compared to fatigue in earlyevenings two months immediately after retirement. In general, the picture is one of increasing fatigue peaking immediately pre retirement, followed by elevated mood immediately post retirement, gradually decreasing to normal pre retirement levels.